Assessing Blood Brain Barrier Permeability in Traumatic Brain Injury Research - George P. Liao; Benjamin M. Aertker; Daniel J. Kota; Karthik S. Prabhakara; Philipp Smith; Robert A. Hetz; Hasen Xue; Supinder Bedi; Scott D. Olson; Charles S. Cox (International Association of Physical Chemists (IAPC), 2015)
The blood brain barrier plays an important role in traumatic brain injury, serving at the crossroads of secondary injury and potential therapies. In regards to trauma, this barrier contains an array of cellular and molecular components that protect the central nervous system from derangements in water homeostasis and inflammation. Preclinical and clinical assays have been developed to describe and quantify blood brain barrier permeability in relation to the integrity of these blood brain barrier components and the handling of edema. This review will discuss both preclinical and clinical molecular and imaging techniques that are used to assess blood brain barrier function and recovery following traumatic brain injury.